Penerapan Pembelajaran Outdoor Learning Sebagai Upaya Meningkatkan Literasi Siswa Di SDN 2 Songgon : Implementasi Kurikulum Merdeka - Giska Medita Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is an implementation activity of the independent curriculum using outdoor learning to increase student literacy. Outdoor learning is learning that is carried out outside the classroom. One of the activities carried out in this learning is word relay, creative wall art, learning tours, word puzzles and many more. The learning carried out aims to hone students' abilities in the field of literacy and increase students' enthusiasm and enthusiasm for learning. The research method used was a mixture/combination. Data collection was carried out using a written test before and after outdoor learning was carried out. This activity was carried out during the Class 6 Teaching Campus assignment period.